Imbalance of redox homeostasis and altered cellular signaling induced by the metal complexes of terpyridine - Katarzyna Malarz; Patryk Ziola; Dawid Zych; Patryk Rurka; Anna Mrozek-Wilczkiewicz (Scientific Reports)
Abstract Compounds that can induce oxidative stress in cancer cells while remaining nontoxic to healthy cells are extremely promising for potential anticancer drugs. 2,2′:6′,2′′-terpyridine-metal complexes possess these properties. The high level of activity (IC50 = 0.605 µM) of 2,2′:6′,2′′-terpyridine-metal complexes on lung, breast, pancreatic, and glioblastoma multiforme cancer lines and their selectivity (SI > 41.32) on human normal fibroblasts were confirmed and presented in this paper. The mechanism of action of these compounds is associated with the generation of reactive oxygen species, which affects several cellular pathways and signals. The results demonstrate that 2,2′:6′,2′′-terpyridine-metal complexes affect cell cycle inhibition in the G0/G1 phase as well as the activation of apoptosis and autophagy cell death. These results were confirmed in several independent studies, including experiments measuring the fluorescence levels of reactive oxygen species, flow cytometry, and gene and protein analysis.